Application of locked nucleic acid-based probes in fluorescence in situ hybridization - Sílvia Fontenete (2016)
Fluorescence in situ hybridization (FISH) employing nucleic acid mimics as probes is becoming an emerging molecular tool in the microbiology area for the detection and visualization of microorganisms. However, the impact that locked nucleic acid (LNA) and 2'-O-methyl (2'-OMe) RNA modifications have on the probe that is targeting microorganisms is unknown. In this study, the melting and hybridization efficiency properties of 18 different probes in regards to their use in FISH for the detection of the 16S rRNA of Helicobacter pylori were compared. For the same sequence and target, probe length and the type of nucleic acid mimics used as mixmers in LNA-based probes strongly influence the efficiency of detection. LNA probes with 10 to 15 mers showed the highest efficiency. Additionally, the combination of 2'-OMe RNA with LNA allowed an increase on the fluorescence intensities of the probes. Overall, these results have significant implications for the design and applications of LNA probes for the detection of microorganisms.